A Time-Motion Study in Intensive Care Unit Using Direct Care Nursing Tool - Arum Pratiwi; MH Dwi Nur Arif; Wisardoyo Wisardoyo; Abi Muhlisin; Dian Hudiyawati (Indonesian Journal of Global Health Research, 2022)
In Nursing, direct care assessment is one of the significant components of nurse performance appraisal and workload identification. The study's purpose is to compare time-motion and the need for direct nursing action between junior and senior nurses in the intensive care unit. This study was conducted for three months in an intensive care unit for 30 nurses. Six investigators observed each nursing direct care action applied by the 34 nurses. Data were collected using the daily log form, then analyzed using descriptive statistics and inferential statistic was independent t test. 35 types of natural care nursing were observed from 30 nurses listed in a nursing daily log. The longest mean time is personal hygiene, with an average time of 14.33 minutes. The shortest average time is respiratory therapy using a nebulizer with a mean of 1.43 minutes. The minimum nursing hours per patient day is 365 minutes (6.08 hours), and the maximum time is 542 minutes (9.03 hours) per day. Direct care means the score is 495 minutes (7.82 hours per day). This study found no significant differences in spending times between senior and junior nurses with t = 0.038, p = 0.970. This study found that the direct nursing action in the intensive care unit is related to nurse workload; this requires the same time for each type of nursing action.